Pathogen Resistance of Transgenic Rice Plants Expressing Mitogen-activated Protein Kinase 1, MK1, from Capsicum annuum - Lee, Da-Eun; Lee, In-Jung; Han, Oksoo; Baik, Myung-Gi; Han, Sung-Sook; Back, Kyoungwhan (Molecules and cells, 2004)
Mitogen-activated protein kinase 1 (MK1) from Capsicum annuum was previously cloned and characterized. MK1 is highly conserved in plants and its amino acid sequence is 92% identical to wound-inducible protein kinase (WIPK) from tobacco. In C. annuum, MK1 is transcriptionally activated by wounding. In the present work, the MK1 gene was introduced into the rice genome by Agrobacterium-mediated transformation. Seven independent transgenic rice plants were isolated and characterized. All seven lines had a single-copy insertion of the MK1 transgene. MK1 mRNA and protein were detected in the transgenic rice, but not in wild type rice. In unwounded transgenic rice plants, the level of jasmonic acid was 3-fold higher than in the wild type, whereas in wounded leaves the level of jasmonic acid was the same in transgenic and wild type plants. Expression of the wound-inducible pathogenesis-related gene PR1a was also higher in transgenic than in wild type plants. Either overexpression of PR1a or increased PR1b and PR10 expression in transgenic rice plants may confer increased resistance to rice blast.